#Crohn's: Historical Cohort of Twitter Activity. Issue 1 (1st October 2020) - Facanali, Marcio Roberto; Bortolozzo Graciolli Facanali, Carolina; Queiroz, Natália Sousa Freitas; Sobrado, Carlos Walter; Nahas, Sérgio Carlos; Safatle-Ribeiro, Adriana Vaz
Abstract: Background: Analysis of the Twitter activity on #Crohn's, identifying individuals with interest in Crohn's disease on Twitter. Methods: A historic cohort study was conducted about Twitter activity evaluation of #Crohn's analyzed over a period of 9 years. For the Twitter analysis, a health-care social media analytics tool, Symplur Signals, was adopted. Results: From 2011 until 2019, 627, 000 tweets of #Crohn's were detected, with 276, 380 retweets by 109, 937 users; of these users, 32.4% were patient advocates and 12.6% were doctors. There was a pattern of annual peak activity of the #Crohn's, mainly in May and December, and less activity, usually in July. Of all tweets, 52.5% were categorized as positive and 47.5% as negative. Conclusions: Social media, especially Twitter, represents an important information tool, but it is still underutilized by gastroenterologists. This study suggests a significant interference of international awareness campaigns about inflammatory bowel disease in the activity of #Crohn's on Twitter, denoting an increase in debating this topic on the platform. Discussions on the subject by health professionals are still below expectations regarding the importance of the theme. Lay Summary: Descriptive article exploring the hashtag #Crohn's on Twitter, relating its activity in a historical and chronological context.